Smart Sewer System Using ESP32 and Send Notifications Through Telegram Bot - Aziz, Rasydan; Yaacob, Megat Satria Zainuddin; Sari, Suhaila (Progress in Engineering Application and Technology, 2023)
Flash flood, commonly known as Flooding that occurs within 6 hours, and frequently within 3 hours cause by heavy or significant rainfall, the intensity of the rainfall, the location and distribution of the rainfall, land use and terrain, vegetation and soil types, and, finally, as a cause of a clogged sewer. In Malaysia, Flash flood frequently happen because of the bad sewer system and clogged sewer that happen by people throwing waste in it. The project's primary purpose is to develop a system that can solve clogged sewer by the mechanism that want been built and send message through telegram bot about the water level in that time and send alert message that water level has been reach highest level and can send message through telegram bot about the waste bin had been full. The microcontroller ESP32 is used for Smart Sewer System. The use of water level sensor is to detect the water level in the sewer, and the use of ultrasonic sensor is to check the level of waste in the waste bin. The ESP32 was used to send alert messages through telegram bot to send warning messages to person in charge about the water level and the waste bin had been full. The system in this project can be improved by making full use of the Internet of Things (IoT) technology facility. In addition, this paper includes a detailed description of the mechanism and system, how it was tested and its performance is presented. There are also the challenges faced in the development of such mechanism and system.